Abundance, Diversity, and Water Quality Assessment of Epilithic Diatoms as Bioindicator in The Dem River, Glothak Waterfall, Wagir District, Malang Regency - Punjungsari, Tyas Nyonita; Ghurry, Muhammad Ainul (Al-Kauniyah: Jurnal Biologi, 2026)
The Dem River, originating from the Coban Glothak Waterfall, is an important water source for local communities. However, the rapid growth of tourism in the Coban Glothak area raises concerns regarding potential water pollution. To evaluate the river’s ecological condition, this study analyzed biological, physical, and chemical parameters with a focus on epilithic diatoms as bioindicators. An exploratory design was applied across three representative stations, each subdivided into three sampling points. Biological analysis involved measuring abundance, diversity, and dominance of diatoms using PAST software. Physical and chemical parameters included temperature, pH, total dissolved solids (TDS), dissolved oxygen (DO), biological oxygen demand (BOD), chemical oxygen demand (COD), nitrate (NO₃), and phosphate (PO₄). Results showed that epilithic diatom abundance was relatively high at all stations, but a decreasing trend was observed from station 1 to station 3, reflecting spatial variations in environmental conditions. The diversity index consistently exceeded 1.5, indicating a fairly diverse diatom community and suggesting supportive water conditions for aquatic organisms. Low dominance values at all stations revealed no species over-dominance, reflecting balanced ecological conditions. Furthermore, the physical and chemical measurements aligned with class 2 and 3 water quality standards, confirming that the Dem River remains suitable for sustaining aquatic life with reasonable diversity.